REVENGE TOURISM: ANALISIS MINAT WISATAWAN PASCA PANDEMI COVID-19 - Annisa Aulya Sudjana; Siti Nur Aini; Hilman Khaerul Nizar (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2021)
This study aims to determine the interest of tourists after the Covid-19 pandemic related to the trend of